Subnational Economic Diplomacy in Resource-Rich Regions: Tin-Based Paradiplomacy by the Bangka Belitung Provincial Government - Ramadhani, Ery; Mohammad Raihan Nadhir (Universitas Muhammadiyah Yogyakarta, 2025)
This study examined the paradiplomatic activities of the Bangka Belitung Provincial Government in attracting international investment to the tin sector. It underscores the growing importance of subnational diplomacy in decentralized, resource-rich regions amidst global imperatives of sustainability and better economic management. It was prompted by the lack of institutional analysis on the utilization of economic diplomacy by local governments in the Global South to rebrand commodities on international markets. Through semi-structured interviews with government representatives, private interests, and civil society stakeholders, supplemented by documentary analysis, a qualitative case study method was pursued. It was performed using the lenses of paradiplomacy, economic diplomacy, and ESG-based governance. Findings uncovered that Bangka Belitung has transitioned from passive natural resource commodity exportation to active international diplomatic branding through the employment of trade missions, advertising campaigns, and memoranda of understanding. However, institutional fragmentation, coordination problems, and the inability to create ESG mechanisms remain as challenges. Despite this, the efforts of the province have testified to increased sensitivity toward international legitimacy as a resource. The study argued that effective subnational diplomacy in natural resource-based economies is contingent upon strategic framing and institutional cohesiveness. Bangka Belitung’s experience could serve as a benchmark for localized diplomacy in the Global South amid the rise of globalized mineral governance.